2014
DOI: 10.5195/jyd.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Relationship Between Media Use and Self-Competence During Adolescence

Abstract: Abstract:The primary goal of this longitudinal study was to examine whether media use predicts adolescent self-competence and/or whether adolescent self-competence predicts media use. The sample included 1,031 10 th and 11 th grade boys and girls from the United States. The adolescents completed a self-report questionnaire in 2007 and 2008 to assess their media use (talking and texting on the phone, listening to music, e-mailing/IMing, playing video games, and working on the computer) and selfcompetence (socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Fewer studies have focused on positive effects that video game play may have on youth. However, recent research has indicated that playing video games is associated with positive self-competence and athletic competence, increased participation in sports, advanced cognitive skills, and more time spent with parents (Adachi & Willoughby, 2015; Añez et al, 2016; Costigan et al, 2013; Green & Bavelier, 2007; Hofferth & Moon, 2012; Ohannessian, 2016; Suchert et al, 2015). Of note, relatively few studies have focused on the link between playing video games and psychological adjustment during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have focused on positive effects that video game play may have on youth. However, recent research has indicated that playing video games is associated with positive self-competence and athletic competence, increased participation in sports, advanced cognitive skills, and more time spent with parents (Adachi & Willoughby, 2015; Añez et al, 2016; Costigan et al, 2013; Green & Bavelier, 2007; Hofferth & Moon, 2012; Ohannessian, 2016; Suchert et al, 2015). Of note, relatively few studies have focused on the link between playing video games and psychological adjustment during adolescence.…”
Section: Introductionmentioning
confidence: 99%